SIFAT FISIKA-KIMIA LEMAK TENGKAWANG DARI EMPAT JENIS POHON INDUK - Raden Esa Pangersa G; Evi Kusmiyati (BRIN Publishing, 2012)
Illipe nut in Indonesia still serves as one of the essential export commodities from the group of non-wood forest products. These nuts unfortunately are traded only in form of the dried fruits. Attempts are necessary to enhance the added value of illipe nuts. Among them is through the processing of the fruit into fat. One manner to extract the fat portion from the illipe- nut fruits is using organic solvent. In relevant, research was conducted on the extraction of illipe-nut fat from its fruit of 4 specier Shorea spp which was originated from the experiment station in Bogor, West Java. Fat extraction was conducted using bexane as the sohvent. The resulting fat was then examined for it physical-chemical properties and sustained the GC- MS (Gas Chromathography-Mass Spectrometry) analysis. The result revealed that the illipe-nut fat from 4 tree species varied in fat yield and its physical-chemical properties (Le. moisture content, acid number, free fatic acid and ind number). The GC-MS analysis indicated that illipe-nut fat contained various saturated fatty acid as well as unsaturated and other chemical compounds, such as phenol, aldebryde, bydrocarbon (aliphatic and cyclic) and hexane (presumably from the organic solvent). Oleic acid is dominant chemical component of S. stenoptera and S. parvifolia, metbyl oleate in S. pinanga and methylene-(4-trimethylsilanyl-phenyl)-amine in S. mecisopteryx.